30.6k views
2 votes
How do i find the inverse of f(x) = (6x + 3)/(x-8)

User Tputkonen
by
4.6k points

2 Answers

3 votes
F-1(x)=3+8x/x-6 this is the inverse
User Christopher Miller
by
4.7k points
3 votes

Answer:
f^(-1)(x)=(8x+3)/(x-6)

Explanation:

To find the inverse, swap the x's and y's and solve for y. Note that f(x) is y.


\underline{\text{Given:}}\\y=(6x+3)/(x-8)\\\\\\\underline{\text{Swap the x's and y's:}}\\x=(6y+3)/(y-8)\\\\\\\underline{\text{Solve for y:}}\\x(y-8)=6y+3\\\\xy-8x=6y+3\\\\xy-6y=8x+3\\\\y(x-6)=8x+3\\\\\large\boxed{y=(8x+3)/(x-6)}

User Tcovo
by
4.9k points